The Effect of Social Capital on Community Empowerment Through Village Fund Management - Florentina Rusmawati Hasim As'ari; Hasim As'ari; Rochmad Bayu Utomo (Cakrawala Repositori IMWI, 2023)
This research was conducted at the Tourism Awareness Group (Pokdarwis) of Nglanggeran Tourism Village, Patuk District, Gunungkidul Regency, D.I.Yogyakarta Province with the following objectives: 1) Knowing the influence of social capital on village fund management; 2) Knowing the effect of village fund management on community empowerment; 3) Knowing the effect of social capital on community empowerment; 4) Knowing the effect of social capital on community empowerment mediated by village fund management. This type of research is quantitative with an associative approach. The population in this study was 80 people who were members of the Tourism Awareness Group (Pokdarwis) of Nglanggeran Tourism Village and used saturated samples. Data analysis techniques use structural equation modeling (SEM), especially Partial Least Square (PLS). The results of this study show that social capital has a significant effect on Village Fund Management, Village Fund Management has a significant effect on Community Empowerment, Social Capital directly does not affect Community Empowerment, but Social Capital will have a significant effect on Community Empowerment if through mediation variables Village Fund Management.